Performance Evaluation of Simulcast vs. Layered Multicasting over Best-effort Networks - Christos Bouras; Apostolos Gkamas; G Kioumourtzis (The 17th International Conference on Software, Telecommunications and Computer Networks (SoftCOM 2009), Split Hvar Korcula, Croatia, 2009)
Multi-rate multicast schemes can be broadly classified into two categories. In layered multicast, a video file is transmitted by a base layer, which contains the most important features of the video. Additional layers, called enhancement layers, contain data that refine the quality of the base layer. In simulcast, the video file is transmitted by replicated layers that contain the same content at different quality. The benefits of layered multicast versus simulcast are still under question, as layered multicast presents higher complexity and more challenging deployment than simulcast. In this paper, two multirate multicast control schemes are compared. The layered multicast SMCC congestion control against our proposed solution for simulcast transmission, named ASSP. We compare the two schemes under a controlled simulation environment with the network simulator software (ns-2) by taking into account the evaluation criteria in RFC 5166. The results demonstrate that both SMCC and ASSP are TCP-friendly while SMCC seems to suffers from small oscillations of the transmission rate. In network topologies with low complexity ASSP consumes no more bandwidth than SMCC for the transmission of the different simulcast streams, while being a simpler solution than the more complicated SMCC.